A Novel Forensic Investigation Applied to Bone Remains Exhumed near to Quirra Interforce Firing Range1. Issue 3 (31st December 2015) - Roncati, Luca; Gatti, Antonietta M.; Capitani, Federico; Bonacorsi, Goretta; Barbolini, Giuseppe; Maiorana, Antonio
Abstract: The need to implement novel techniques, able to support a causal link between exposure and pathology, has been emerged over the recent years. The application of scanning electron microscope coupled with probe X‐ray microanalysis (by means of an energy‐dispersive spectroscopy) has been developed by our research group for the bone remains investigation. It was aimed to testify the exposure to microsized and nanosized pollutions, due to military activities in the Quirra interforce firing range, of a Sardinian shepherd, died of acute leukemia. Metallic debris with a combustive morphology and with an oncogenic potential has been surely detected inside his bone marrow canal. This novel technique has proved to be able to bring to light a source of past exposure preserved over time within the bone marrow canal. It can be useful for postmortem analyses, delivering a new avant‐garde approach to modern forensic science.